Marcos ; Stay or not stay The other side [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
A debate between loyalists, oppositionists to have the remains of the former President Ferdinand E. Marcos burried in the Philippines ; also discusses the issue of the American bases in the Philippines ; an interview with Corazon Aquino.
Marcos (10 min.) -- To stay or not to stay (15 min.) -- The other side (15 min.)
VHS.
Keywords: Marcos, Ferdinand E., 1917-1989 -- Death and burial; Aquino, Corazon Cojuanco, 1933.; Military bases, American -- Philippines